Surprise, Recipes for Surprise, and Social Influence. (7th February 2018) - Loewenstein, Jeffrey
Abstract: Surprising people can provide an opening for influencing them. Surprises garner attention, are arousing, are memorable, and can prompt shifts in understanding. Less noted is that, as a result, surprises can serve to persuade others by leading them to shifts in attitudes. Furthermore, because stories, pictures, and music can generate surprises and those can be widely shared, surprise can have broad social influence. People also tend to share surprising items with others, as anyone on social media has discovered. This means that in addition to broadcasting surprising information, surprising items can also spread through networks. The joint result is that surprise not only has individual effects on beliefs and attitudes but also collective effects on the content of culture. Items that generate surprise need not be random or accidental. There are predictable methods or recipes for generating surprise. One such recipe is discussed, the repetition‐break plot structure, to explore the psychological and social possibilities of examining surprise. Recipes for surprise offer a useful means for understanding how surprise works and offer prospects for harnessing surprise to a wide array of ends. Abstract : This paper discusses the role that surprises play in persuasion and shifts in attitudes, as well as collective effects of surprise on the content of culture through stories, pictures, and music. The author notes that items that generate surprise need not be random or accidental, and discusses, in particular, the repetition‐break plot structure as a useful means for understanding how surprise works, and how it can be harnessed.